Long-Term Outcome of Landau-Kleffner Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The types of language disorders in 4 young adults with Landau-Kleffner syndrome were analyzed at long-term follow-up at the National Institute of Mental Health, National Center of Neurology and Psychiatry, Chiba, Japan.